(untitled) (Jurnal Teknologi Industri Pertanian, 2018)
Pangandaran district is a district that has the third largest coconut tree plantation area in West Java, and coconut is made as one of the potential regional prime commodities. This research objective was to discover four aspects on coconut agroindustry, namely the availability of raw material, distribution, product’s prospective, and economic empowerment of society. The method used in this research was descriptive method, while survey and questionnaire spreading were used. To find out the potential availability of raw materials, secondary data were used,which were proceeded with forecasting moving average method. Spreading of coconut agroindustry was mapped for several sub-districts, according to primary or secondary data. Determination of prospective product were done by Technique for Order Performance of Similarity to Ideal Solution (TOPSIS). Potential of economic empowerment was obtained by analysis of profit cost ratio. Refer to the research results, coconut agroindustry had big potential in empowerment of the social economy. This potency can be seen by the amount of availability and certainty of coconut as raw material, the quality of the resulting coconut, availability of human resources, breadth of market section, infrastructure and means of transportation, supporting by local people, then government policy that supporting in growth and development of coconut agroindustry. The coconut agroindustry was spread in a whole sub-disctrict, and the most of it was located in Cimerak Sub-District. The most prospective product was coconut sugar, that is one of products that have big potential and profitable for empowerment of the social economy. Keywords: agroindustry, coconut, economic empowerment, Pangandaran Regency